Wheelset/Rail Geometric Characteristics Assessment with Regard to Wheelset Rolling - Gerlici, Juraj; Lack, Tomas (Communications - Scientific letters of the University of Zilina, 2005)
The geometric relation between a wheelset and a rail is assessed with the help of geometric characteristics. Geometric characteristics are: equivalent conicity function, delta r function placement of contact points of a wheelset and a rail, tangent gamma function and effective conicity. It turned out that these characteristics are at present the most important not only for the judgment of ride characteristics of a vehicle on the rail but also for the wearing of wheel treads and rail heads, e. i., for the assessment of the track and vehicles in order to find out the current state and for the assessment of changes of the wheels and rails profile shapes in order to improve the current state too. The process of geometric characteristic assessment of a wheelset and rail with regard to wheelset rolling is analysed in the article.